2022
DOI: 10.1007/s11482-022-10048-w
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Work-Home Culture and its Relations with the Work–Family Interface and Employees’ Subjective Well-being

Abstract: The two studies reported in this paper aimed to present and discuss both the validation of the Work-Home Culture (WHC) scale (Dikkers et al., Work & Stress, 21(2), 155–172, 2007) in the Italian context (Study 1), and a relational model that links the WHC to subjective well-being via the mediation of three facets of the work-home interface: work-family conflict, work-family enrichment and work-family balance (Study 2). Heterogeneous samples of workers from different organisations took part in the cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…They improved productivity with less working hours and improved their WLB. Bobbio et al (2022) analyzed WFH cultures. They concluded that firms and managers who acknowledge the challenges of WFH setup and provide necessary support to employees, both technological and mental, enjoy higher employee engagement, satisfaction and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They improved productivity with less working hours and improved their WLB. Bobbio et al (2022) analyzed WFH cultures. They concluded that firms and managers who acknowledge the challenges of WFH setup and provide necessary support to employees, both technological and mental, enjoy higher employee engagement, satisfaction and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the future of WFH might help business leaders shape organizational culture, adopt structures and organize resources to support efficiency and performance (Bobbio et al , 2022). It can also contribute to rebuilding organizational trust, which in the LATAM context might be a significant factor in building high–performance organizations (Coria-Sánchez, 2016; La Falce et al , 2020).…”
Section: Contribution To Business Practicementioning
confidence: 99%
See 1 more Smart Citation
“…It is present when workers have positive emotions that outweigh the negative ones when they perceive high levels of satisfaction, and in turn, they are more performing (De Simone et al 2022;Taris and Schaufeli 2015). In literature, subjective well-being at work is associated with numerous constructs that can predict and positively impact it (i.e., Babic et al 2020;Bobbio et al 2022;Garg and Singh 2020;Kumar 2020;Lee et al 2021). However, other situations may adversely affect subjective well-being and negatively impact it, especially when workers need to adapt to new situations that they have never experienced before (Bellini et al 2022a(Bellini et al , 2022b(Bellini et al , 2023.…”
Section: Introductionmentioning
confidence: 99%